Analysis Of The Leading Sector Of ‘Kota Pelajar’ With Location Quotient Method And Klassen Typology - Prabowo, Dhinnessa (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
This research aims to identify and analyze the leading economic sectors for economic growth in Yogyakarta City. The analysis in this study uses data from the Regional Gross Domestic Product (GDP) for the years 2017-2021. The Location Quotient (LQ) analysis method is employed to determine the leading sectors and their growth potentials. Additionally, the study uses Tipology Klassen analysis to categorize sectors based on their growth patterns and economic structures. The results indicate that Yogyakarta City has several dominant sectors, with 11 out of 17 sectors classified as leading sectors or bases. These dominant sectors include the Manufacturing Industry, Electricity and Gas Supply, Water Supply, Waste Management, and Recycling, Financial and Insurance Services, Real Estate, Government Administration, Defense, and Social Security, Education Services, Health and Social Activities, Accommodation and Food Services, Information and Communication, and Business Services. The research recommends that the Yogyakarta City government prioritize the development of these sectors to foster economic growth and enhance competitiveness.